Examining the Structural Validity of the Strengths and Difficulties Questionnaire (SDQ) in a U.S. Sample of Custodial Grandmothers - Palmieri, Patrick A. (2007)
The authors examined the structural validity of the parent informant version of the Strengths and Difficulties Questionnaire (SDQ) with a sample of 733 custodial grandparents. Three models of the SDQ’s factor structure were evaluated with confirmatory factor analysis based on the item covariance matrix. Although indices of fit were good across all 3 models, a model that included a newly hypothesized positive construal method factor in addition to the 4 symptom factors (Emotional Symptoms, Conduct Problems, Hyperactivity-Inattention, Peer Problems) and the single Prosocial Behavior factor originally intended for the SDQ provided the best representation of this instrument’s latent structure. Structural validity was further evidenced by measurement invariance across grandparent race and grandchild gender and age, a conceptually meaningful pattern of cross-scale correlations, and the acceptable internal reliability estimates found for each subscale. Measurement and clinical implications of the results are discussed.